Early recurrence of well‐differentiated (G1) neuroendocrine liver metastasis after curative‐intent surgery: Risk factors and outcome. Issue 7 (27th September 2018) - Xiang, Jun‐Xi; Zhang, Xu‐Feng; Weiss, Matthew; Aldrighetti, Luca; Poultsides, George A.; Bauer, Todd W.; Fields, Ryan C.; Maithel, Shishir Kumar; Marques, Hugo P.; Pawlik, Timothy M.
Abstract : Background: The objective of the current study was to identify the risk of early vs late recurrence of well‐differentiated (G1) neuroendocrine liver metastasis (NELM) after curative‐intent resection. Methods: Patients who underwent curative‐intent resection for well‐differentiated NELM were identified from a multi‐institutional database. Clinicopathological details, as well as the long‐term overall (OS) and recurrence free survival (RFS) were obtained and compared. The optimal cutoff value to differentiate early and late recurrence was determined to be 1 year based on trend curve analysis. Results: Among the 548 patients undergoing curative resection for NELM, 162 patients had a well‐differentiated NELM. After a median follow‐up of 69 months, 59 (36.4%) patients had tumor recurrence; 23 (39.0%) patients recurred within 1 year (early recurrence) after surgery, while 36 (61.0%) recurred after 1 year (late recurrence). Early recurrence was associated with worse outcome vs late recurrence (5‐year OS, 72.4% vs 92.0%; P  = 0.020) and no recurrence (5‐year OS, 72.4% vs 100.0%; P  < 0.001). In addition, postrecurrence survival was worse within 36 months after recurrence among patients who recurred early compared with patients who recurred late (survival after recurrence at 36 months: early recurrence, 71.6% vs late recurrence, 91.4%; P  = 0.047), although survival was comparable at 60 months (early recurrence, 71.6% vs late recurrence, 70.0%; P  = 0.304). On multivariable analysis, nonfunctional neuroendocrine tumors (hazard ratio [HR], 4.4; 95% confidence interval [CI], 1.2‐16.7; P  = 0.029) and lymph node metastasis (HR, 3.6; 95% CI, 1.1‐11.1; P  = 0.028) were independent risk factors for early recurrence, whereas lymph node metastasis (HR, 3.0; 95% CI, 1.2‐7.8; P  = 0.020) and R1 resection (HR, 3.9; 95% CI, 1.4‐10.5; P  = 0.008) were independently associated with late recurrence. Conclusions: Roughly, one‐third of patients with well‐differentiated NELM experienced a recurrence following curative‐intent surgery. Among patients who recurred, two out of five patients recurred within 1 year after surgery. Early recurrence of well‐differentiated NELM was associated with the hormone functional status and lymph node metastasis.